WAR IN THE ANCIENT SOCIAL GROUPS OF COSTA RICA: LITHIC SCULPTURES IN THE LIGHT OF ETHNOHISTORICAL SOURCES AND ORAL TRADITION - Sánchez Avendaño, Viviana (2023)
We discuss warfare practice in Costa Rica’s ancient social groups through the study of stone sculptures, ethnohistoric sources, and indigenous oral tradition accounts. First, some proposals on the subject made by professionals in archeology are reviewed. Then, discusses how war is presented in both historical sources and oral tradition. Finally, archaeological evidence is interpreted from the statuary in the Museo Nacional de Costa Rica, the Museo del Jade y la Cultura Precolombina and the Museo del Oro Precolombino collections. The study highlights the importance of the warrior figure within the social stratification of past societies, as well as the fact that war constituted a constant and permanent activity between the groups.